Special issues in breast cancer gene expression profiling in breast cancer - Nasser, Selim M. (2009)
• Gene expression profiling has been increasingly used to determine new cancer markers. This technology holds major promises for improving the management of patients with breast cancer in which traditional clinicopathologic parameters do not account for all the heterogeneity of this disease and its distinct prognostic groups. Gene expression profiling has resulted in new classification of breast cancer and new assays are being developed and commercialized as prognostic and predictive tests. However, the use of these tests in a clinical setting presents many issues. The accuracy of this new technology is often overestimated and its limitations should be addressed. Although early results are promising, further validation and well designed clinical trials are required before incorporating these tests in routine clinical practice.